PENGARUH KONFLIK PEKERJAAN-KELUARGA DAN BEBAN KERJA TERHADAP STRES KERJA DALAM MENINGKATKAN KINERJA PEKERJA WANITA PADA PERUSAHAAN GARMEN YANG DIAKUISISI DI SEMARANG - Eldes Willy Filatrovi (JURNAL ILMIAH EDUNOMIKA, 2021)
The purpose of this research is to investigate the effects of family work conflict, work stress, work load and work performance. The study was conducted at women workers in the acquired garment. Data is processed using the Structural Equation Modelling (SEM) which assisted by application program of Analysis of Moment Structure (AMOS) version 18.0. According to the analysis, it is concluded as the followings: family work conflict has a positive effect on work stress (CR =6,061); work load has a positive effect on work stres (CR = 2,793); family work conflict has a not effect on work performances (CR = -0.899); work load has a negative effect on work performances (CR =-3,123) and work stres has a negative effect on work performances(CR =-3,908) Keyword : Work Conflict, Work Stres, Work Load, Work Performances